TEACHING WRITING IN JORDAN: WHAT SHOULD BE? - Abdelkareem Saleem Alhaddad (European Scientific Journal, ESJ, 2014)
In Jordan, writing is taught as part of language teaching in general. Teachers, whose role in the learning process is central, insist on mastery of mechanical skills and are seldom concerned with meaning and creativity. In the context of Jordan, writing is the skill that most students are least proficient in. The research literature reveals that the traditional approach to writing instruction does not work. New methods of teaching should be implemented. If writing becomes a central element in language curriculum, then the writing process approach is likely to play a major role in writing instruction in Jordan. By focusing on the process of writing, as well as the product, teachers can encourage students to enjoy writing and find it relevant to their lives. This will make them more fluent writers. Implementation of such a program will require little money, but much courage and patience.